Relación entre funcionalidad familiar y estrés en adolescentes del Bachillerato. Zona 7, Ecuador 2016. - Nagua Carrión, Edwin Fabricio (2017)
Family functionality is an interactive and systemic dynamic of the family, which is exposed to several modifying factors; one of them, which affects all its members and is currently on the rise, is stress. Adolescents are one of the most susceptible groups to this because stress can cause them innumerable biological, psychological and social problems. This research establishes the relationship between family functionality and stress in high school adolescents from the provinces of El Oro, Loja and Zamora Chinchipe in Ecuador. A non-experimental quantitative study was carried out through the application of self-completion questionnaires including a FFSIL Family Functional Test and a PSS 14 test for stress perception. In order to select educational institutions that met the inclusion criteria the Educational Institutions Master File (AMIE) pertaining to the Ministry of Education was checked. Subsequently, using a simple random probabilistic sampling through Microsoft Excel 960 teenagers aged 15 to 19 years old, who attend the 1st, 2nd or 3rd year of high school were pre-validated. The results indicated that adolescents from dysfunctional families were two times more likely to present stress than those from functional families. Both genders presented similar significance. Key words: Dysfunctionality, family, youth, stressor